2003
DOI: 10.1023/b:doop.0000005339.23258.8f
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the electroretinogram resulting from discontinuation of vigabatrin in children

Abstract: Electroretinograms (ERGs) have been recorded longitudinally in children before and during treatment with the antiepileptic drug vigabatrin for the past 3.5 years. Vigabatrin induced changes in ERG responses occur in children; the most dramatic changes occur in the oscillatory potentials. The purpose of this study was to identify changes in ERG responses associated with discontinuation of vigabatrin treatment. If vigabatrin-induced changes reverse after discontinuation of the drug we infer that the original cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
2
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 45 publications
6
35
2
2
Order By: Relevance
“…Similar results have been reported by Krakow et al [23]. A recent study [24] has shown increased amplitudes in both photopic and scotopic oscillatory potentials after discontinuation of vigabatrin, but they interpret these changes as a non-toxic pharmacological effect of vigabatrin on GABAergic amacrine cells in the inner retina.…”
Section: Introductionsupporting
confidence: 88%
“…Similar results have been reported by Krakow et al [23]. A recent study [24] has shown increased amplitudes in both photopic and scotopic oscillatory potentials after discontinuation of vigabatrin, but they interpret these changes as a non-toxic pharmacological effect of vigabatrin on GABAergic amacrine cells in the inner retina.…”
Section: Introductionsupporting
confidence: 88%
“…20,21 For example, oscillatory potentials decrease in amplitude during drug treatment but recover after discontinuation of the drug, unlike the decrease in flicker amplitude, which is less likely to recover. 22 Most children in the HSC longitudinal study do not show the form of retinal nerve fiber layer atrophy described in these 3 more advanced cases of retinal toxicity. Of interest is the tendency, reported by the parents of these children, to stare straight ahead rather than look normally about their visual environment.…”
Section: Discussionmentioning
confidence: 91%
“…Because a variety of ERG parameters (amplitude and implicit time) change during vigabatrin treatment, the current studies are helping to clarify which of these changes represent nontoxic side effects and which correlate with drug toxicity. [20][21][22] Changes in oscillatory potential amplitude result, at least in part, from non-toxic changes. 22 Conversely, if the ERG, particularly the 30-Hz flicker response, decreases more than expected from intervisit variability, both the clinical assessment and the ERG are repeated within 3 months.…”
Section: Participants and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…59 Numerous investigators have reported the prevalence in children to be well below that of adults, 91,96,98,99 suggesting a prevalence of approximately 20% in this younger population. The best data on infants 65,71,73,100 have established a prevalence of approximately 40%, with incidence of 16% as assessed by the highly sensitive electroretinogram (ERG) 30-Hz flicker amplitude. The prevalence of cone B-wave amplitude abnormalities, the other vigabatrin-specific ERG parameter that is sensitive and specific for the vigabatrin-induced defect, is about 20%, with an incidence of 4%.…”
Section: Prevalence Onset and Progression Of Vfd With Vigabatrinmentioning
confidence: 99%